2009
DOI: 10.1186/1471-2458-9-46
|View full text |Cite
|
Sign up to set email alerts
|

Potential determinants of obesity among children and adolescents in Germany: results from the cross-sectional KiGGS study

Abstract: Background: Obesity among children and adolescents is a growing public health problem. The aim of the present paper is to identify potential determinants of obesity and risk groups among 3-to 17-year old children and adolescents to provide a basis for effective prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
156
0
43

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(222 citation statements)
references
References 49 publications
(46 reference statements)
23
156
0
43
Order By: Relevance
“…In KOPS parental overweight and obesity were found as main determinants of overweight risk in German children and adolescents (Table 4), as in other studies (10)(11)(12)(13)(14) . By contrast, in the literature the impact of lifestyle factors was not uniform.…”
Section: Determinants Of Prevalencesupporting
confidence: 79%
“…In KOPS parental overweight and obesity were found as main determinants of overweight risk in German children and adolescents (Table 4), as in other studies (10)(11)(12)(13)(14) . By contrast, in the literature the impact of lifestyle factors was not uniform.…”
Section: Determinants Of Prevalencesupporting
confidence: 79%
“…34,[40][41][42][43][44] Data collected in a German health interview of 13,450 obese/overweight children found that obesity was strongly related to both low SES and parental obesity. 45 Similarly, low SES backgrounds in conjunction with high amounts of television viewing put children at a higher risk for being overweight. 46,47 Other aspects of SES have also been examined.…”
Section: Sleepmentioning
confidence: 99%
“…Nos Estados Unidos, no ano de 2002, 65,7% da população adulta apresentava excesso ponderal, e entre aqueles com idade de seis a 19 anos, 31% e 16% tinham sobrepeso e obesidade, respectivamente. Em estudo com crianças e adolescentes alemãs, constatouse que, em menos de duas décadas, o sobrepeso apresentou elevação de 50%, e o percentual de obesos duplicou 4,5 cou, resultando em 49% de indivíduos com sobrepeso e 14,6% com obesidade. Chama a atenção a alarmante prevalência em crianças (47,8%) e adolescentes (21,5%), os quais apresentaram incrementos percentuais de três e quatro vezes ao longo do mesmo intervalo de tempo 6 .…”
Section: Introductionunclassified